Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Simulasi Virtual Terhadap Penguasaan Konsep dan Kreativitas Fisika Siswa SMAN 2 Mataram - Shinta Mutiara Dewi; Ahmad Harjono; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This research is a quasi-experimental aims to identify the effect of problem-based learning model using virtual simulation media towards the studentsÃ¢â¬â¢ concept mastery and creativity in physics. The design of this research used of non-equivalent control group design, while the sampling technique used purposive sampling. The population of this research is all students of grade X SMAN 2 Mataram, while the sampling are the students of grade X-3 as the experimental group and the students of grade X-4 as control group. The data obtained in this research isÃÂ  data mastery of concept and creativity. The research hypothesis was tested using t-test polled variances. The test result showed that the N-gain mastery of concepts has increased in each sub material and the highest increase in the sub matter theory of electromagnetic waves. Values of N-gain experimental group in the high category (71%) and control group in the medium category (53%). T-test showed that the model is applied to significant influence on improving studentsÃ¢â¬â¢ mastery of concepts and creativity, higher in the experimental group compared with the control group. Increased figural creativity higher than verbal creativity in both classes